Teacher Training Scaffolding Type to Improve Teacher’s Ability in Development of Guided Inquiry Practical Worksheet - Rosid, A; Sunarya, Y; Arifin, M (KnE Social Sciences, 2019)
Generally teacher training is still ineffective, and there are still many weaknesses in its implementation. The main objective of teacher training is to improve the ability and skills in learning process, so as to prepare students for competition in the millennial century. In chemistry learning teachers must be able to stimulate all initiatives, creativity and scientific attitudes through guided inquiry-based laboratory activities. The purpose of this study was to measure the effectiveness of teacher training in improving the ability to develop guided inquiry lab worksheets to achieve students’ understanding and literacy. The training involved 26 chemistry teachers who teach in Karawang West Java. The method applied in this study is multi-method, both quantitative and qualitative with multi-design. The results achieved in this study indicate that the teacher’s response to training materials and training methods is very strong based on the results of the pretest and posttest. Increased ability of teachers in inquiry is classified as medium category. In general, the teacher’s response to the training showed a very positive response especially to the topic of practical evaluation or evaluation. Some teachers demonstrated their ability to design guided inquiry-based lab worksheets mainly related to contextual phenomena, including the effect of vinegar acid concentration on baking soda decomposition reactions, and the effect of fertilizer concentrations on grain sprout growth Teacher training is still a project that many considered as not effective and has a number of shortcomings. Learning should prepare students according to the demands of the 21st century. So that the learning process of chemistry should stimulate initiative, creativity, and scientific attitude through Guided-Inquiry based laboratory activity to improve student literacy ability. The objective of this research is to measure the effectiveness of teacher training in improving the production ability of Guided-inquiry Labs to achieve students’ understanding and literacy. The training involved 26 chemistry teachers as trainees, a mixed method chosen to measure the quantitative side by preexperimental design with a pretest-posttest design, one-group design and teacher feedback collection on training through questionnaires. The pretest and posttest results were calculated by measuring N-gain, and scoring teacher responses on a scale of 1-4. The results of questionnaire showed that the teachers responded with strong criteria and very strong, with an average of 83 (Very Strong). Increased ability of participants is shown with N-gain obtained by each teacher. The average N-gain of trainees is 0.71 in the medium category. Aspects of analyzing the curriculum have the smallest N-gain value compare to the aspects of composing the referring questions and aspects of presenting the experimental data in the form of tables/graphs. In general, teachers’ responses to training show very strong categories with the highest responses on the topic of practicum assessment. And the ability of teachers in designing guided-inquiry self-study worksheets has improved especially for aspects of curriculum analysis and presenting experimental data in the form of tables/graphs. The development of teachers’ skills through measurable training that focused on improving teacher competence should be more frequent. The selection of materials that are urgently needed and used in the learning process should also be considered. Keywords: guided inquiry, LKS, rate of reaction, student worksheet, scientific literacy, training, scaffolding